Evaluation of Coastal Tourism Development in Muna District in Tenggara Sulawesi - La Ode Kadar (LPPM Universitas Negeri Jakarta, 2020)
Abstract This study aims to obtain the results of a survey of the evaluation of marine tourism development in Muna Regency in Southeast Sulawesi. The unit of analysis in this research is the Department of Tourism and Culture as one of the government agencies in Muna Regency, which is required to manage and contribute to the maximum revenue contribution to Regional Original Income (PAD) with selected respondents and critical informants is the Head of the Service, Head of Division and Head of Sub Division of Planning and Finance. The research method used is the descriptive qualitative method. The analytical tool used is the Realistic Evaluation Method with the Context-Mechanism-Outcome configuration approach. The results of the study show that the evaluation of marine tourism development in Muna Regency through an evaluation analysis of the Context and Mechanism can be obtained Outcomes: (a) several development programs that have been carried out by the Tourism and Culture Office, both destination development programs, marketing development, and creative economy development have been successfully implemented ( b) The Department of Tourism and Culture has several gaps that must be corrected to achieve advanced and reliable management and development of marine tourism. Keywords: Evaluation, Development, and Marine Tourism.